Arisan Menurun Online dalam Perspektif Hukum Islam Kontemporer - Nur, Anita; Sastrawati, Nila (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to determine the implementation of online social gatherings, and to understand the views of contemporary scholars regarding the implementation of online social gatherings. This type of research. is library research, the approach used is sociological and syar'i. The implementation of online social gathering declines by disseminating information through online media, then engaging the participants with the procedures and conditions that have been determined by the arisan maker. Among them the members/participants can know each other or not because of limitations through virtual or media that limit it so it is difficult to get to know each other. The implementation of this online descending social gathering was found to violate Islamic law or not in accordance with the provisions of Islamic law, namely in it there was an element of qardh/debts that should have been debts that made the system help each other with the principle that the number of withdrawals and the number of payments must be the same. This declining arisan also causes one thing that is not fair. Arisan is essentially a loan agreement where the first member receives the money collected from the loans of other members who have not received it